Sari kacang hijau sebagai makanan pendamping ASI (MP-ASI) dalam upaya pencegahan stunting - Purnama, Robby Candra; Lutfianawati, Dewi; Nira, Isnaini Luqi; Novalia, Wayan Ayu; Putri, Yolanda Anisa Kadil (JOURNAL OF Public Health Concerns, 2023)
Background: After the age of 6 months the baby is started to be given Complementary food for breast milk (MP-ASI) is food that is easy to consume and digest by babies. MP ASI given must provide additional nutrition to meet the nutritional needs of a growing baby. Although breast milk is the best food for babies, babies >6 months old need more vitamins, minerals, protein, and carbohydrates. This high nutritional need cannot only be obtained from breast milk, but also requires additional complementary foods. One type of complementary food for breastfeeding (MP-ASI) that can be given by infants and toddlers is green bean juice. Purpose: To increase respondents' knowledge about the benefits and processing of mung bean juice as complementary food for breast milk (MP-ASI) for infants and toddlers. Method: In this counseling using demonstration and lecture methods. Results: Respondents can know and understand the benefits of mung bean juice and can make their own mung bean juice as complementary food for breast milk (MP-ASI) for infants and toddlers to prevent stunting. Conclusion: Respondents can know and understand the benefits of mung bean juice and can make their own mung bean juice as complementary food for breast milk (MP-ASI) for infants and toddlers to prevent stunting. Keywords: Complementary Foods for Breastfeeding; Green Bean Extract;  Prevention of Stunting Pendahuluan: Setelah berusia 6 bulan bayi mulai di berikan Makanan pendamping ASI (MP-ASI) adalah makanan yang mudah dikonsumsi dan dicerna oleh bayi. MP ASI yang diberikan harus menyediakan nutrisi tambahan untuk memenuhi kebutuhan gizi bayi yang sedang bertumbuh. Walaupun ASI merupakan makanan terbaik bagi bayi, bayi berusia >6 bulan membutuhkan lebih banyak vitamin, mineral, protein, dan karbohidrat. Kebutuhan gizi yang tinggi ini tidak bisa hanya didapatkan dari ASI, tetapi juga membutuhkan tambahan dari makanan pendamping ASI. Salah satu jenis makanan pendamping ASI (MP-ASI) yang bisa diberikan oleh bayi dan balita yakni sari kacang hijau. Tujuan: Meningkatkan pengetahuan responden tentang manfaat dan pengolahan sari kacang hijau sebagai makanan pendamping ASI (MP-ASI) bagi bayi dan balita. Metode: Dalam penyuluhan ini menggunakan metode demonstrasi dan ceramah. Hasil: Responden dapat mengetahui dan memahami manfaat sari kacang hijau serta dapat membuat sendiri sari kacang hijau sebagai makanan pendamping ASI (MP-ASI) bagi bayi dan balita guna pencegahan stunting. Simpulan: Responden dapat mengetahui dan memahami manfaat sari kacang hijau serta dapat membuat sendiri sari kacang hijau sebagai makanan pendamping ASI (MP-ASI) bagi bayi dan balita guna pencegahan stunting.